An analysis of Trust Mechanism and Strategies of Public Welfare Crowdfunding Platforms under the Perspective of Digital Governance A Case Study Based on Shuidichou - Chen Siying (COMMICAST, 2025)
With the deep penetration of digital technology into the philanthropic sector, public welfare crowdfunding platforms such as Shuidichou have become an important channel for public participation in social assistance. However, recurring problems including false fundraising claims, information asymmetry, and opaque fund flows have triggered frequent trust crises, posing serious challenges to the sustainability of public welfare crowdfunding and digital governance. Addressing how trust can be reconstructed through institutional arrangements, technological systems, and communication strategies has therefore become a critical issue. Drawing on a three-dimensional theoretical framework of interpersonal trust, institutional trust, and digital trust, this study aims to examine the internal logic and practical pathways of trust construction on the Shuidichou platform. Using a qualitative case study approach, the research analyzes platform function updates, interface design, governance measures, and authoritative media reports related to trust construction from 2016 to 2025. The findings reveal that trust on Shuidichou is generated through the dynamic inter-embedding of interpersonal, institutional, and digital trust. Interpersonal trust is expanded and mediated through social crowdfunding mechanisms and platform authentication, institutional trust is reinforced through transparent governance, participatory mechanisms, and risk control systems; and digital trust is established through multi-modal technologies that ensure transparency and verifiability. These dimensions interact synergistically rather than operating independently. This study concludes that trust construction in public welfare crowdfunding is a dynamic and governance-driven process. By elucidating the co-evolution of multi-dimensional trust mechanisms, the research contributes to the literature on digital trust and provides practical insights for optimizing trust governance and policy innovation in public welfare crowdfunding platforms.